Vous êtes sur la page 1sur 4

Table A-1 Laplace Transform Pairs

F(s)
m
1 U n i t i mp u l s e 8 ( f) 1

1
2 Unit step 1(f)
s
1
3 f
s2
fn -1 1
4
(n - 1)! (n
= 123 P )
sn

n!
5 fn (n = 1, 2, 3,...)
s n+ 1

1
6 e -af
s+a

1
7 f e -af
(s + a)2

1
8 1
(n - 1)!f
n- 1 - af
e (n - W, - )
(s + a)n
n!
9 f ne -af (n = 1, 2,3,...) ( s + a ) n+ 1

v
10 sin vf
s2 + v2
s
11 cos vf
s + v2
2

v
12 sinh vf 2 2
s - v

s
13 cosh vf 2 2
s - v

11 1
14 (1 - e - af) a s(s + a)
1
1
15 ( e - af e - bfB (s + a)(s + b)
b - a
1 s
16 ( b e - bf - a e - af) (s + a)(s + b)
b-a
17 11 1
1 + ( b e - af - a e - bf) s(s + a)(s + b)
ab a - b
(continues on next page)

Appendix A / Laplace Transform Tables 863


Table A-1 (continued)

18 i 1
- (1 - e - at - ate - at) a
s(s + a) 2

19 1
(at - 1 + e - at) a- 1
2
2
s (s + a)
v
20 e -at sin vt
(s + a) 2 + v 2

s+a
21 e -at cos vt
(s + a) 2 + v 2

22 e z n t sinv nVl Z 2t (0 < Z < 1) 2


21 - z2 2
S + 2z^ nS + 2

e z n t sin (v nVl Z 2 1 f)
Vl - z 2
s
23 Vl - z 2 2
1 s + 2zv ns + w /
1
f - tan z

(0 < z < 1 , 0 < f < p/ 2 )


1
1 e z n t sin (v n V1 z -t + f)
V 1 - z2
2
24 , t - V 1 - z2
f tan 1 s(s 2 + 2z^ ns + V/)

(0 < z < 1 , 0 < f < p/ 2 )

25 1 cos vt v2
s(s 2 + v 2)

26 vt sin vt v3
s (s + v 2)
2 2

27 sin vt vt cos vt 2v 3
(s + v 2) 2
2

28 1 . s
t sin vt 2v
(s + v 2) 2
2

29 t cos vt
s 2 - v 2 (s 2 + v 2) 2
2 2 (cos v 1 t cos v 2t) (v 1 Z 2)
30 s
W2 ^1
(s 2 + 2)(s 2 + v 2)
1 s2
31 -(sin vt + vt cos vt) 2v 3 ;
(s 2 + v 2) 2

864 Appendix A / Laplace Transform Tables


Table A-2 Properties of Laplace Transforms
1 l [ A/(t) ] = AF(s)
2 l/1(t) / 2 (t) ] = F(s) F 2 (s)

3 1; d/(t) J = sF(s) - /(0 )


d2
4 l; = s 2 F(s) - s/(0 ; ) - /(0 ; )
/ J
5 l; ' d n .. (k -1 )

s n F(s) - 2 s n -k /(0 )
=
_ dt n/(t ) k =1
(k -1) d k -1
whe re /(t )
= dtk - 1 /(t )
1 F(s) 1
6 l; = S+ s / /(t) d t
J /(t) dt s s t =0 ;
i; /" / /( (dt) n
7 - F s ( . s) + 2 s . +, / J/(t)(dt) k A
s k =1 S t =0
8 ir i F(s)
/ /(t) dt = S
q q 0s

9 /(t) dt = limF(s) if /(t) dt exists


0sS00
10 1 [ e - '/(t) ] = F(s + fl)

11 1[ /(t - a )1(t - a ) ] = e -a S F(s) a > 0


dF ( s )
12 [ -
1 t /<t ]= ds
d2
13 1 [ t /(t) ]
2 =
dn
14
1 [ t n /(t) ] = (- 1) n F(s) (n = 1,2,3, ... )
q
1 1
15
1 y /(t) = F(s) ds if lim /(t) exists
tS0t
s
16
_ (l )J =
1 / aF(as)

17 J/i(t - t )/ (t ) dt J = Fi(s)F2(s)
2
0
1 c +j q
18 1 [ /(t ) g (t ) ] -
= 2p j J F( P )G(s P) dP

Appendix A / Laplace Transform Tables 865


Finally, we present two frequently used theorems, together with Laplace transforms
of the pulse function and impulse function.
Initial value theorem f(0+) = hm/W = } ^s F ( s )

Final value theorem f ( q = /hs, = IS


) /( t) s F ( s )

Pulse function
A AA
m =A-t(f) - - 1( t -1 )0 0
M M
0 iC f(t) ] = -------- e- st0
t 0s t 0s
Impulse function A

g(t) = lim , for 0 < t < to A


(t)]
M
o
h0
to 1
rh 0
[g = lim (1 - e-st ) 0

0 t0 i
= 0, for t < 0, t0 < t
4 -[ A ( 1 - e - )]st0 dt
0
= lim
M S0
0 d
dt0 (t" s)

---A
s

866 Appendix A / Laplace Transform Tables